1982
DOI: 10.1007/bf01872275
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular potential and K+ activity in rat kidney proximal tubular cells in acidosis and K+ depletion

Abstract: Techniques were developed for the measurement of intracellular potentials and potassium activities in rat proximal tubule cells using double barreled K+ liquid-ion-exchanger microelectrodes. After obtaining measurements of stable and reliable control values, the effects of K+ depletion and metabolic and respiratory acidosis on the intracellular potential and K+ activity in rat kidney proximal tubular cells were determined. At a peritubular membrane potential of -66.3 +/- 1.3 mV (mean +/- SE), intracellular K+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 32 publications
3
27
1
Order By: Relevance
“…Observations in the cortical collecting tubule (23) suggest that acidosis decreases potassium conductance in this structure. Similar effects of acidosis have been reported for the proximal convoluted tubule (24) and the medullary thick ascending limb of Henle (mTALH) (25). Recent work in the mTALH suggests that sodium chloride entry depends on potassium conductance and luminal potassium cotransport (26,27).…”
Section: Resultssupporting
confidence: 75%
“…Observations in the cortical collecting tubule (23) suggest that acidosis decreases potassium conductance in this structure. Similar effects of acidosis have been reported for the proximal convoluted tubule (24) and the medullary thick ascending limb of Henle (mTALH) (25). Recent work in the mTALH suggests that sodium chloride entry depends on potassium conductance and luminal potassium cotransport (26,27).…”
Section: Resultssupporting
confidence: 75%
“…The lack of effect on bicarbonate reabsorption in the hypokalemic rats of the present study may have various explanations. Factors likely to stimulate bicarbonate reabsorption that have been defined in the proximal tubule could involve the following: (i) stimulation of Na'-H' exchange, secondary to the intracellular acidosis that has been reported in hypokalemia (42,43) and stimulation of an Hf-sensitive modifier site (44); (ii) activation of basolateral Na'-HCO3 cotransport (45); (iii) hyperpolarization of the basolateral membrane with an increase in the driving force for bicarbonate exit (46). While none of these factors have been identified in any the segments of the LOH, it is probable that they are operative in hypokalemia.…”
Section: Resultsmentioning
confidence: 99%
“…With a stoichiometry of three equivalents of HCO3 ions/Na+ ion, membrane depolarization should decrease, whereas hyperpolarization should increase the rate of base extrusion via Na+:CO"-:HCO-cotransport. Using a double barrel microelectrode, Cemerikic et al (49) have shown that potassium deficiency induces hyperpolarization of the basolateral membrane of proximal tubule cells. Therefore, it is possible that changes in membrane potential induced by potassium depletion could be responsible for the increased activity of the Na+:CO3 :HCO-cotransporter observed in our studies.…”
Section: Resultsmentioning
confidence: 99%